Learning from Clusters A Critical Assessment from an Economic-Geographical Perspective - Boschma, Ron A.; Kloosterman, Robert C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
The topic of clustering is a central one in contemporary debates on the relationship between the global and the local. This book addresses both conceptual and empirical issues on clustering, learning and regional development. It represents the current state of affairs in this body of literature in a critical way and gives a unique overview of the latest developments. The book reflects a kind of uneasiness scholars have with the general model of clusters that has been so dominant in the field of regional economics and economic geography in the past twenty years. All chapters in this book contribute to the debate, either at the conceptual level, the empirical level or both. At the conceptual level, the cluster model has been criticized because it has been represented as a model that has been idealized too much. Moreover, it has been developed mainly as a theoretical model, without having been accompanied by a great deal of empirical testing of its main propositions.
The 'Cluster' Model -- A Systematic Perspective on Local Development -- Cluster Dynamics -- Embedded Local Growth: A Theory Taken too Far? -- Beyond the Learning Region: The Dialectics of Innovation and Culture in Territorial Development -- Economic Development, Institutions and Trust -- Social Capital and Regional Development: An Empirical Analysis of the Third Italy -- Regional Innovation Systems, Varieties of Capitalism and Non-Local Relations: Challenges from the Globalising Economy -- Delirious Rotterdam: The Formation of an Innovative Cluster of Architectural Firms -- Competitiveness in Regional Clusters. The Case of Océ's 'Knowledge Industry Clustering' Project -- Clustering, Learning and Regional Development -- The Impacts of ICT and Externalities on Urban Development -- Urban Milieux: From Theory to Empirical Findings -- The Spatial Clustering of Knowledge-Intensive Services: Computing Services in the Netherlands -- Dynamic Information Externalities and Employment Growth in the Netherlands -- New Regional Economics: About Virtual Agglomeration Effects -- 'Old' and 'New' Economy and Services -- Economic Capabilities and Strategic Clusters: New Perspectives for National and Regional Economic Policy -- Concluding Remarks -- Further Learning from Clusters.
Keywords: GEOGRAPHY; GEOGRAPHY; ECONOMIC GEOGRAPHY; GEOGRAPHY (GENERAL).